EP10 Community first responders' contribution to rural emergency medical service provision in the UK. Issue 9 (23rd August 2022) - Botan, Vanessa; Asghar, Zahid; Rowan, Elise; Smith, Murray D; Patel, Gupteswar; Phung, Viet-Hai; Trueman, Ian; Spaight, Robert; Brewster, Amanda; Mountain, Pauline; Orner, Roderick; Siriwardena, Aloysius Niroshan
Abstract : Background: Community First Responders (CFRs) are volunteers dispatched by Emergency Medical Services (EMS) to potentially life-threatening emergencies to provide care until the ambulance staff arrive. Previous qualitative research described CFRs' role, perceptions, and motivations, but quantitative evidence on their contribution to rural healthcare provision is lacking. We aimed to investigate the number, types, and location of calls (rural or urban), and characteristics of patients attended. Methods: We used a retrospective observational design analysing routine data from six of ten ambulance services in England during 2019. Descriptive statistics were used to directly compare incidents where CFRs attended first with attendances from ambulance staff. A multiple logistic regression model was used to identify the main predictors of CFR attendance. Results: The data included 4.5 million incidents over one year. CFRs attended first a significantly higher proportion of calls in rural areas compared to urban areas (3.90% vs 1.48%, p<0.05). The main predictors of CFR presence were rurality (Odds Ratio [OR] 2.05, 95% Confidence Interval [CI] 1.99-2.11, p<0.001), conditions including cardiorespiratory (OR 9.20, 95%CI 5.08-16.64, p<0.001) or neurological/endocrine (OR 9.26, 95%CI 5.12-16.77, p<0.001) and the most urgent call category 1 (OR 5.19, 95%CI 3.86-6.99, p<0.001) and call category 2 (OR 4.44, 95%CI 3.31-5.96 p<0.001). CFRs were also less likely to attend patients from minority ethnic backgrounds, those younger than 39 years, and incidents in more deprived areas. Conclusions: CFRs play an important role in EMS delivery, supporting the work of ambulance services, especially in rural areas. The work of CFRs has expanded from its original purpose to attend out-of-hospital cardiac arrest to more types of emergencies. Future development of CFR schemes should prioritise training for a range of conditions, and access to more deprived and ethnically diverse areas.